Evaluation of a distance education radio farm school programme in India: Implications for scaling up - Sasidhar, P. V. K.; Suvedi, Murari; Vijayaraghavan, K.; Singh, Baldev; Babu, Suresh Chandra (SAGE Publications, 2011)
Distance education radio programmes on poultry farming with registered participants were organized using the local language in an effort to link researchers to rural poultry farmers through radio broadcasts. This study, based on data from 74 participants and 60 non-participants, assesses the impact of the radio farm school on participants using Bennett's hierarchy. Information gathered from the participants included the inputs used, the production activities carried out, the outputs obtained and the reactions of the participants with respect to listening behaviour, opinions, knowledge, attitudes, adoption changes and SWOT parameters. Overall, the evaluation found that the farm school on radio with registered participants had a major impact on developing awareness, knowledge and changes in attitude and in involving end-users in outreach activities. The related implications for scaling up and harnessing the medium of radio to disseminate outreach information are discussed.